Examining Variability in Values Attributed to Culture: Using Personality as a Relative Benchmark. (August 2016) - Ng, Vincent; Woo, Sang Eun; Tay, Louis; Foster, Jeff
Prior work examining the role of cultural groupings (i.e., national membership) on personal values showed small to moderate amounts of variability attributable to culture, refuting the idea that culture determines values. We extend this research by examining the proportion of variance in values that could be explained by cultural membership. Because there is no definitive level of proportion of variance that would lead to a conclusion that values are culturally determined, personality, which is arguably not culturally determined, was used as a relative benchmark. Language groups were used as an alternate conception of cultural groupings. A large data set of 144, 857 workers from across 31 major language groups revealed that language groups explained a significant and non-negligible amount of variance in personal value dimensions (7%-17%). Nevertheless, this was not significantly larger than any single personality dimension (3%-12%). In other words, our data failed to support the notion that personal values are strongly determined by cultural groupings compared with personality.